Abstract 214: Predictors of Mechanical Thrombectomy Success and Failure: A Preliminary Analysis - Phoebe Johnson‐Black; Faisal Mukarram; Amir Molaie; Yasmin Ghochani; Jeffrey Saver; Viktor Szeder (Stroke: Vascular and Interventional Neurology)
Introduction Mechanical thrombectomy (MT) is now the standard of care in treatment of large vessel occlusion (LVO) in acute ischemic stroke (AIS). However, a significant minority of patients do not achieve successful recanalization. Previous case series’ have reported failed recanalization at a rate of approximately 12% (1). In the present study, we investigated clinical and procedural characteristics predictive of MT success and failure. Methods We conducted a retrospective analysis of MT patients with LVO presenting to our academic comprehensive stroke center from 2015‐2020. Recanalization failure was defined as TICI 0‐2a and success as TICI 2b‐3. We compared all 49 consecutive failure cases to a random selection of 85 successful MT cases. Demographic, clinical, procedural, and outcome data were compared between the two groups. Results In this cohort, there was no statistically significant difference in sex, pre‐stroke modified Rankin score (mRS), admission National Institutes of Health Stroke Scale (NIHSS), door‐to‐groin time, thrombolytic use, or site of occlusion between the two groups. In the success group, patients were older (76 vs 61, p=0.003), and had a higher average number of atherosclerotic risk factors (p=0.002). There was a higher proportion of embolic stroke of undetermined source (ESUS) in the success group compared with the failure group (8.5% vs 0%, p=0.039). A higher proportion of failure cases were due to large artery atherosclerosis (30.6% vs 19.5%, p=0.12) and cardioembolism (55.1% vs 67.1%, p=0.27), though neither of these differences were statistically significant. Stent‐retrieval alone (SR) was a more common first pass technique in failed than in successful MT (14.3% vs 0%, p=0.001). Conclusion This study investigated clinical and procedural factors associated with successful and failed recanalization in MT. In this cohort, stent‐retrieval alone as a first pass technique was more commonly associated with failed MT. Stroke etiology was associated with rates of failure, with a significantly higher proportion of ESUS in successful cases and a trend toward a higher proportion of large vessel atherosclerosis and cardioembolism in failed MT.